السرطان Arcaniaelongata Yokoya, 1933 نوع جديد من القشريات عشاريات الأرجل المهاجرة من فصيلة Leucosiidae إلى البحر المتوسط - حسن, حسان (Latakia University Journal -Biological Sciences Series, 2018)
A new alien crab A.elongata collected from the Syrian waters in the coast of Jableh at depth of 45 to 60 m. A single female ovigerous specimen of this specieswas recorded in the Eastern coast of the Mediterranean. The specimens were identified following Galil (2001a). The description of Naruse (2014) was also consulted. The Leucosiid crab is the first alien species from the genus Arcania arrived in the Mediterranean Sea and the fourth species from the Leucosiidae family established in the coast of Syria with IxaLeach, 1816; ColeusiaGalil, 2006; Myra Leach, 1817 (Hasan, 2008c). نوع جديد من السرطانات الغريبة A.elongata جمع من المياه البحرية السورية في شاطئ جبلة على عمق 45-60 م. تم جمع عينة واحدة (أنثى تحمل بيوض) من هذا النوع على الساحل الشرقي للبحر الأبيض المتوسط، و قد صنفت هذه العينة باتباع المفاتيح التصنيفية المعتمدة من قبل Galil (2001a) ، كما تم الاعتماد على الوصف المقدم لهذا النوع من قبل Naruse (2014). إن هذا النوع من السرطانات هو أول نوع مهاجر من جنس Arcania يصل إلى البحر الأبيض المتوسطو الرابع من فصيلة Leucosiidae التي أنشأت مجتمعات على الشاطئ السوري و هي الأنواع التالية:Ixa Leach, 1816; ColeusiaGalil, 2006; Myra Leach, 1817 حسب الدراسات السابقة (Hasan, 2008c).